Influence of drill bit diameter on drilling of polyurethane foams - Teixeira, T. (2018)
Drilling is one of the most common processes involved in machining operations. The usual requirement is the efficient material removal. However, when it comes to the living tissues, drilling assumes greater attention to ensure a minimally invasive procedure. This work describes conventional drilling experiments performed on solid rigid polyurethane foams with similar mechanical properties to the human bone. An extensive experimental study was conducted to evaluate the effects of different drill diameters (4, 5 and 6 mm) on the temperature rise and stresses generation during drilling process. Different experimental tests were performed to assess their repeatability. Results from the experiments suggest that both drilling temperatures and stress level increased with increase in the drill tool diameter.